The Responses of the World Health Organization to Pandemics and Dangerous Epidemics - Tzagkarakis, Stylianos Ioannis; Douki, Stamatina (HAPSc Policy Briefs Series, 2022)
Pandemics are major threats to human life and have occurred throughout human history. It should be made clear that the term epidemic refers to disease outbreaks that occur in a human population over a given period of time to a greater than expected extent. It may be geographically confined to a place or an entire country. In the event that the epidemic spreads outside the geographical boundaries of a country, it is defined as a pandemic. This study focuses on the contribution of the World Health Organisation in preventing and responding to major pandemic crises. A focus will be placed on the management of pandemic crises or risks, namely HIV, cholera (in Yugoslavia in the 1970s), SARS-CoV, H1N1, Ebola and SARS-CoV2.